THE CATEGORY OF TYPOLOGICAL CORRELATION IN ENGLISH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article analyzes the theoretical arguments of linguists and scientists about the category of typological correlation in English and Uzbek languages. In addition, the author tried to determine the category of correlation using examples using fiction in English and Uzbek.